Cardiac involvement in congenital myotonic dystrophy. Issue 2 (February 1990) - Forsberg, H; Olofsson, B O; Eriksson, A; Andersson, S
Abstract : Seven young patients (mean age 19 years 8 months) with congenital myotonic dystrophy and with defined symptoms at birth were investigated by electrocardiography and echocardiography. None had cardiovascular symptoms. Electrocardiograms or echocardiograms or both were abnormal in all patients. Atrioventricular and intraventricular conduction defects were the most common electrocardiographic abnormalities and were seen in five patients. The echocardiographic examinations showed impaired left ventricular systolic function in one patient. Other echocardiographic findings were a small left ventricle and atrium, minor valve defects, and mitral valve prolapse. This study shows that the heart is often affected in young patients with congenital myotonic dystrophy. The specialised conduction system is often affected and so too is the myocardium, causing impaired systolic function.